Volume dan Kapasitas Jaringan Jalan di Kawasan Pondok Labu - Djamaluddin, Said; Siregar, Adella Hotnyda; Hendratmoko, Pungkas (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2015)
Â TheÂ intent Â of Â this Â study Â to Â analyze Â the Â optimization Â of Â highway Â network Â of Â hospitals Fatmawati to Pondok Labu (UPN âVeteranâ Jakarta). Especially for measuring the ratio of the volume and capacity (V/C) of the facilities and infrastructure, given the congestion level above the tolerance within 2-3 km of the RS Fatmawati-UPN